Chlamydia trachomatis prevalence in the Greater Accra region and the Western region of Ghana - Dela, Helena (2016)
A thesis submitted to Department of Clinical Microbiology, School of Medical Sciences, Kwame Nkrumah University of Science and Technology (KNUST) in partial fulfillment of the requirement for the award of Master of Philosophy Clinical Microbiology degree, 2015